Influence of COPD on the Diaphragm and Muscles of the Lower Limbs - Meridj, A; Belaala, R; Djeghri, Y (Journal of Pulmonology and Respiratory Research, 2024)
Agusti A, Celli BR, Criner GJ, Halpin D, Anzueto A, Barnes P, et al. Global initiative for chronic obstructive lung disease 2023 report: GOLD executive summary. Am J Respir Crit Care Med. 2023;207(7):819-837. Available from: https://doi.org/10.1164/rccm.202301-0106pp Murray CJL, Aravkin AY, Zheng P, Abbafati C, Abbas KM, Abbasi-Kangevari M, et al. Global burden of 87 risk factors in 204 countries and territories, 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019. Lancet. 2020;396(10258):1223-1249. Available from: https://pubmed.ncbi.nlm.nih.gov/33069327/ Ho T, Cusack RP, Chaudhary N, Satia I, Kurmi OP. Under- and over-diagnosis of COPD: a global perspective. Breathe (Sheff). 2019;15(1):24-35. Available from: https://doi.org/10.1183/20734735.0346-2018 Buist AS, Vollmer WM, McBurnie MA. Worldwide burden of COPD in high- and low-income countries. Part I. The Burden of Obstructive Lung Disease (BOLD) Initiative. Int J Tuberc Lung Dis. 2008;12(7):703-708. Available from: https://pubmed.ncbi.nlm.nih.gov/18544191/ Halpin D, Celli B, Criner G, Frith P, Varela L, Salvi S, et al. The GOLD Summit on chronic obstructive pulmonary disease in low- and middle-income countries. Int J Tuberc Lung Dis. 2019;23(11):1131-1141. Available from: https://doi.org/10.5588/ijtld.19.0397 Rehman AU, Hassali MAA, Muhammad SA, Harun SN, Shah S, Abbas S. The economic burden of chronic obstructive pulmonary disease (COPD) in Europe: results from a systematic review of the literature. Eur J Health Econ. 2020;21(2):181-194. Available from: https://doi.org/10.1007/s10198-019-01119-1 Uzaslan E, Mahboub B, Beji M, Nejjari C, Tageldin MA, Khan JA, et al. The burden of chronic obstructive pulmonary disease in the Middle East and North Africa: results of the BREATHE study. Respir Med. 2012;106(Suppl). Available from: https://doi.org/10.1016/s0954-6111(12)70014-8 Khelafi R, Aissanou A, Tarsift S, Skander F. Épidémiologie de la bronchopneumopathie chronique obstructive dans la wilaya d’Alger. Rev Mal Respir. 2011;28(1):32-40. Available from: http://dx.doi.org/10.1016/j.rmr.2010.06.026 Decramer M, Janssens W. Chronic obstructive pulmonary disease and comorbidities. Lancet Respir Med. 2013;1(1):73-83. Available from: https://doi.org/10.1016/s2213-2600(12)70060-7 Waschki B, Kirsten A, Holz O, Muller K-C, Meyer T, Watz H, et al. Physical activity is the strongest predictor of all-cause mortality in patients with COPD: a prospective cohort study. Chest. 2011;140(2):331-42. Available from: https://doi.org/10.1378/chest.10-2521 Spruit MA, Gosselink R, Troosters T, Kasran A, Gayan-Ramirez G, Bogaerts P, et al. Muscle force during an acute exacerbation in hospitalized patients with COPD and its relationship with CXCL8 and IGF-I. Thorax. 2003;58(9):752-756. Available from: https://doi.org/10.1136/thorax.58.9.752 Van Vliet M, Spruit MA, Verleden G, Kasran A, Van Herck E, Pitta F, et al. Hypogonadism, quadriceps weakness, and exercise intolerance in chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2005;172(9):1105-1111. Available from: https://doi.org/10.1164/rccm.200501-114oc Coronell C, Orozco‐Levi M, Mendez R, Ramirez‐Sarmiento A, Galdiz J, Gea J. Relevance of assessing quadriceps endurance in patients with COPD. Eur Respir J. 2004;24(1):129-136. Available from: https://doi.org/10.1183/09031936.04.00079603 Vestbo J, Prescott E, Almdal T, Dahl M, Nordestgaard BG, Andersen T, et al. Body mass, fat-free body mass, and prognosis in patients with chronic obstructive pulmonary disease from a random population sample: findings from the Copenhagen City Heart Study. Am J Respir Crit Care Med. 2006;173(1):79-83. Available from: https://doi.org/10.1164/rccm.200506-969oc Seymour J, Spruit M, Hopkinson N, Natanek S, Man W-C, Jackson A, et al. The prevalence of quadriceps weakness in COPD and the relationship with disease severity. Eur Respir J. 2010;36(1):81-88. Available from: https://doi.org/10.1183/09031936.00104909 Bernard S, LeBlanc P, Whittom F, Carrier G, Jobin J, Belleau R, et al. Peripheral muscle weakness in patients with chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 1998;158(2):629-634. Available from: https://doi.org/10.1164/ajrccm.158.2.9711023 Nici L, Donner C, Wouters E, Zuwallack R, Ambrosino N, Bourbeau J, et al. American Thoracic Society/European Respiratory Society statement on pulmonary rehabilitation. Am J Respir Crit Care Med. 2006;173(12):1390-1413. Available from: https://doi.org/10.1164/rccm.200508-1211st Pitta F, Troosters T, Spruit MA, Probst VS, Decramer M, Gosselink R. Characteristics of physical activities in daily life in chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2005;171(9):972-977. Available from: https://doi.org/10.1164/rccm.200407-855oc Marquis K, Debigare R, Lacasse Y, LeBlanc P, Jobin J, Carrier G, et al. Midthigh muscle cross-sectional area is a better predictor of mortality than body mass index in patients with chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2002;166(6):809-813. Available from: https://doi.org/10.1164/rccm.2107031 Maynard-Paquette A-C, Poirier C, Chartrand-Lefebvre C, Dube B-P. Ultrasound evaluation of the quadriceps muscle contractile index in patients with stable chronic obstructive pulmonary disease: relationships with clinical symptoms, disease severity and diaphragm contractility. Int J Chron Obstruct Pulmon Dis. 2020;15:79-88. Available from: https://doi.org/10.2147/copd.s222945 McCool FD, Tzelepis GE. Dysfunction of the diaphragm. N Engl J Med. 2012;366(10):932-42. Available from: https://doi.org/10.1056/nejmra1007236 Charloux A, Enache I. Exploration fonctionnelle des muscles respiratoires. EMC-Pneumologie. 2015;12(3):1-11. Available from: https://www.em-consulte.com/article/983785/exploration-fonctionnelle-des-muscles-respiratoire De Blasio F, Comune M, Oliva A, Garello L, Bucca C, Prota R. Influence of diaphragm dysfunction, exercise capacity, and nutrition on dyspnea severity of COPD patients. Chest. 2020;157(6). Available from: http://dx.doi.org/10.1183/13993003.congress-2020.1025 Similowski T, Yan S, Gauthier AP, Macklem PT, Bellemare F. Contractile properties of the human diaphragm during chronic hyperinflation. N Engl J Med. 1991;325(13):917-923. Available from: https://doi.org/10.1056/nejm199109263251304 Levine S, Nguyen T, Kaiser LR, Rubinstein NA, Maislin G, Gregory C, et al. Human diaphragm remodeling associated with chronic obstructive pulmonary disease: clinical implications. Am J Respir Crit Care Med. 2003;168(6):706-713. Available from: https://doi.org/10.1164/rccm.200209-1070oc Barreiro E, De La Puente B, Minguella J, Corominas JM, Serrano S, Hussain SN, et al. Oxidative stress and respiratory muscle dysfunction in severe chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2005;171(10):1116-1124. Available from: https://doi.org/10.1164/rccm.200407-887oc Levine S, Gregory C, Nguyen T, Shrager J, Kaiser L, Rubinstein N, et al. Bioenergetic adaptation of individual human diaphragmatic myofibers to severe COPD. J Appl Physiol. 2002;92(3):1205-1213. Available from: https://doi.org/10.1152/japplphysiol.00116.2001 Barnes PJ. Oxidative stress in chronic obstructive pulmonary disease. Antioxidants. 2022;11(5):965. Available from: https://doi.org/10.3390%2Fantiox11050965 Scicchitano BM, Pelosi L, Sica G, Musaro A. The physiopathologic role of oxidative stress in skeletal muscle. Mech Ageing Dev. 2018;170:37-44. Available from: https://doi.org/10.1016/j.mad.2017.08.009 Lage VKdS, de Paula FA, dos Santos JM, Costa HS, da Silva GP, Lima LP, et al. Are oxidative stress biomarkers and respiratory muscle strength associated with COPD-related sarcopenia in older adults? Exp Gerontol. 2022;157:111630. Available from: https://doi.org/10.1016/j.exger.2021.111630 Sepulveda‐Loyola W, Osadnik C, Phu S, Morita AA, Duque G, Probst VS. Diagnosis, prevalence, and clinical impact of sarcopenia in COPD: a systematic review and meta‐analysis. J Cachexia Sarcopenia Muscle. 2020;11(5):1164-1176. Available from: https://doi.org/10.1002/jcsm.12600 Wormser J, Lebret M, Le Neindre A. L’échographie du diaphragme: principes et intérêts pour le kinésithérapeute. Kinésithérapie, la Revue. 2017;17(182):62-70. Available from: https://doi.org/10.1016/j.kine.2016.11.009 Gethin-Jones TL, Noble VE, Morse CR. Quantification of diaphragm function using ultrasound: evaluation of a novel technique. Ultrasound Med Biol. 2010;36(11):1965-1969. Available from: https://doi.org/10.1016/j.ultrasmedbio.2010.08.003 Matamis D, Soilemezi E, Tsagourias M, Akoumianaki E, Dimassi S, Boroli F, et al. Sonographic evaluation of the diaphragm in critically ill patients: technique and clinical applications. Intensive Care Med. 2013;39(5):801-810. Available from: https://doi.org/10.1007/s00134-013-2823-1 Kim WY, Suh HJ, Hong S-B, Koh Y, Lim C-M. Diaphragm dysfunction assessed by ultrasonography: influence on weaning from mechanical ventilation. Crit Care Med. 2011;39(12):2627-2630. Available from: https://doi.org/10.1097/ccm.0b013e3182266408 Epelman M, Navarro OM, Daneman A, Miller SF. M-mode sonography of diaphragmatic motion: description of technique and experience in 278 pediatric patients. Pediatr Radiol. 2005;35(7):661-667. Available from: https://doi.org/10.1007/s00247-005-1433-7 Richard P. Exploration du diaphragme: l’échographie est incontournable. Rev Mal Respir. 2017;34(6):645-660. Available from: http://dx.doi.org/10.1016/j.rmr.2017.02.005